KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KECERDASAN SPASIAL SISWA SMP NEGERI 3 BANYUMAS - Tanzani, Muhammad Afif (AlphaMath : Journal of Mathematics Education, 2018)
This research aimed to describe students’ mathematical reasoning ability viewed from spatial intelligence in SMP Negeri 3 Banyumas. This was conducted in Grade VIII A SMP Negeri 3 Banyumas. The method of this research was qualitative descriptive. The sampling technique was purposive sampling. The subjects were divided into three groups; group with high spatial intelligence, group with medium spatial intelligence, and group with low spatial intelligence. The techniques of collecting data were test and interview. The result of this research shows that: (1) Students with high spatial intelligence were able to master six indicators of mathematical reasoning ability such as proposing presumption, finding the pattern to make generalization, drawing conclusion from the statements, proving the truth of a solution, doing mathematic manipulation, and checking the validity of an argument; (2) Students with medium spatial intelligence were able to master four indicators of mathematical reasoning ability such as proposing presumption, finding the pattern to make generalization, doing mathematic manipulation, and checking the validity of an argument; and (3) Students with low spatial intelligence were able to master three indicators of mathematical reasoning ability such as proposing presumption, drawing conclusion from the statements, and doing mathematic manipulation. KEY WORDS: Mathematical Reasoning Ability, Spatial Intelligence